Maintenance management of local authority building (Majlis Bandaraya Melaka Bersejarah) / Nur Hidayu Zorkafli - Zorkafli, Nur Hidayu (Faculty of Architecture, Planning and Surveying, 2009)
MBMB(Majlis Bandaraya Melaka Bersejarah )mostly the biggest name in Melaka. The major function of MBMB is to take care of its own authority. MBMB have their own objective which is to make Majlis Bandaraya Melaka Bersejarah a strong, dynamic, and excellent organization,to become the main force in shaping the Historical City of Melaka in terms of development and appeal,to maximize the services to the community and last but not least to unite the community more effectively. The objective of this research are There are some objectives that have to be achieved in order to complete this research. Among them are to study the current practice of maintenance management in government building of Majlis Bandaraya Melaka Bersejarah(MBMB),to identify the problems occur in maintenance management system, to know the satisfaction/perception of the users/occupants to recommend the solutions for* the problems. The research done to identify the current practise of maintenance use by Majlis Bandaraya Melaka Bersejarah(MBMB) and to determine the problems that always occured in MBMB management system. Research also been done to know the real situation of maintenance program in MBMB. Methodologies of this dissertation involved 3 main steps which is by distributing questionnaire, interview the staff at the maintenance department and observation of the buildings at the site. But the first step is by discussing with supervisor no how to make this dissertation complete and success, list down all activity that must be attached to this dissertation and make references from books and internet. The conclusion is MBMB have their own maintenance program and that program must be research in order to get the best satisfaction among their building occupant and last but not least they need strong organization chart as a guide to their staff.